Needs Analysis of Integrated Ethno-Socioscientific Multimedia to Enhance Elementary Students’ Environmental Awareness - Helga Salsabila; Agus Mukti Wibowo; Samsul Susilawati (Experiment: Journal of Science Education, 2026)
This research is driven by the "knowledge-behavior gap" among students at MI Baipas Malang, where high environmental knowledge does not translate into real-world action. The study aims to conduct a need assessment for developing multimedia based on Ethno-Socioscientific Issues (Ethno-SSI) to enhance students' environmental awareness. Adopting the Analysis phase of the Lee and Owens model, this qualitative descriptive study used student questionnaires and teacher interviews. Findings show that students are visual-digital learners who require interactive content linked to Malang’s local wisdom, such as water spring preservation (punden). Although school technology is supportive, current materials lack socioscientific dilemmas to trigger critical thinking. In conclusion, developing Ethno-SSI multimedia is urgently needed to bridge the gap between understanding and action through cultural relevance and digital technology. This analysis serves as the foundation for the upcoming design and implementation stages. Key Words: Need analysis; Ethno-Socioscientific Issues; Multimedia; Environmental Awareness;